Zirconia Ceramics
Ruconia ceramics, with their specific composition and molar ratios, overcome the high-temperature and low-strain rate limitations of existing superplastic zirconia ceramics by achieving high-speed superplasticity at temperatures below 1350°C and high strain rates.
Patent Information
- Application Number
- JP2021097672
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-11
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2041-06-11
AI Technical Summary
Existing superplastic zirconia ceramics require high temperatures (1350-1550°C) and low strain rates to achieve tensile elongation of 200% or more, which is not suitable for industrial applications that require high-speed superplasticity at lower temperatures.
The development of Ruconia ceramics, which consist of tetragonal zirconia with specific compositions of yttrium, magnesium, titanium, and aluminum, along with a molar ratio of titanium oxide to magnesium oxide between 0.7 and 5.6, and a molar ratio of aluminum oxide to magnesium oxide between 0.1 and 0.3, allowing for superplasticity at temperatures below 1350°C and high strain rates.
Ruconia ceramics achieve tensile elongation of 200% or more at high strain rates (1×10^-2 /s or higher) at temperatures as low as 1200°C, significantly reducing the lower limit temperature for superplasticity and enabling high-speed superplasticity in the low-to-medium strain rate range.
Smart Images

Figure 0007673957000003 
Figure 0007673957000001 
Figure 0007673957000002
Abstract
Description
[Technical field]
[0001] The present invention , J More specifically, the present invention relates to a ceramic material made of tetragonal zirconia, which, when densely sintered, has excellent strength, toughness, wear resistance, and heat resistance, and exhibits excellent superplastic tensile ductility even in a high strain rate region. Ruj Regarding Luconia ceramics. [Background technology]
[0002] Since the discovery of superplasticity similar to that of metallic materials in yttria (Y2O3) stabilized tetragonal zirconia (Y-TZP), which is considered to be the toughest monolithic ceramic, there have been hopes for technological developments that would allow it to be formed near-net like metallic materials. However, the manifestation of superplasticity in Y-TZP requires temperatures of 1350-1550°C and a temperature of 10 -5 ~10 -4 A combination of low strain rates in the / s range is necessary.
[0003] This is because the strain rate is in the low range of 1.0×10 -4 For example, in the case of a speed of 1.0×10 / s, it takes 170 minutes to stretch a material with an initial length of 10 mm to 20 mm. -3 / s (processing time 17 min), and more preferably, 1.0 × 10 -2 The material is required to have a tensile elongation of 200% or more at high speeds of 1.7 min / s or more (high speed superplasticity (JIS H 7007:2002)).
[0004] In this specification, 1.0×10 -2 / s or more 1.0×10 -1 / s, the high strain rate range is 1.0×10 -3 / s or more 1.0×10 -2 The strain rate range of less than 1.0×10 / s is defined as the medium strain rate range. -3 The strain rate range of less than 1 / s is called the low strain rate region.
[0005] For the purpose of industrial applications, various improved Y-TZP have been proposed (see, for example, Patent Documents 1-3 and Non-Patent Documents 1-2). Patent Document 1 and Non-Patent Document 1 disclose a superplastic zirconia-based sintered body characterized by the addition of magnesium oxide and titanium oxide to partially stabilized zirconia containing yttrium oxide. However, even the superplastic zirconia-based sintered bodies of Patent Document 1 and Non-Patent Document 1 have a high strain rate region of 1.0×10 -2 At 1350°C / s, the minimum temperature at which superplasticity appears is 1350°C.
[0006] Patent Document 2 describes a sintered body in which one or more types of spinel phases represented by the general formula MgAl2O4, MnAl2O4, or TiMn2O4 are uniformly dispersed in a zirconia matrix, the total of the zirconia phase and the spinel phase being 80% by volume or more, each having an average crystal grain size of 2.0 μm or less, and a sintering rate of 1×10 -4 However, even the zirconia-based superplastic ceramic of Patent Document 2 has a tensile ductility of 200% or more at a strain rate of 1.0×10 / s or more. -2 At 1000 / s, the minimum temperature at which superplasticity appears is 1400°C.
[0007] Non-Patent Document 2 reports that a tetragonal zirconia sintered body to which 5 mass% (equivalent to 13 vol%) of amorphous SiO2 was added had a 1×10 -3 However, even in the case of the tetragonal zirconia sintered body of Non-Patent Document 2, the -2 At high strain rates of 100 / s, the minimum temperature at which superplasticity appears is 1400°C.
[0008] Patent Document 3 discloses a ceramic bulk material consisting of an aggregate of ceramic nanocrystalline particles that are one or more oxides selected from aluminum, magnesium, potassium, lithium, sodium, calcium, zinc, yttrium, scandium, samarium, indium, uranium, chromium, zirconium, tin, tungsten, tantalum, iron, nickel, cobalt, copper, niobium, vanadium, manganese, molybdenum, and lanthanum. However, the temperature at which superplasticity appears has not been investigated, and suitable composition conditions for the appearance of high-speed superplasticity have not been identified. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2001-146469 A [Patent Document 2] JP 2004-107156 A [Patent Document 3] JP 2004-143039 A [Non-patent literature]
[0010] [Non-Patent Document 1] Y. Sakka et al., Advanced Engineering Materials, vol. 5, 2003, 130-133 [Non-Patent Document 2] K. Kajihara et al., Acta metall.mater., Vol. 43, 1995, 1235-1242 Summary of the Invention [Problem to be solved by the invention]
[0011] From the above, the object of the present invention is to achieve a 1×10 -2 Achieves tensile elongation of 200% or more at high strain rates of 100 / s. RujIn particular, the present invention provides a ruconia ceramic having a thermal conductivity of 1×10 -2 The present invention aims to provide a superplastic zirconia ceramic that achieves tensile elongation of 200% or more at a high strain rate region of 1 / s or more. Another object of the present invention is to provide a superplastic zirconia ceramic that exhibits superplasticity at a lower temperature than conventional materials in a low to medium strain rate region. Ruj To provide Luconia ceramics. [Means for solving the problem]
[0012] The present invention Noji The zirconia ceramic contains 90 vol% or more of tetragonal zirconia (ZrO2), yttrium (Y) in a range of 1 mol% to 4 mol% in terms of yttrium oxide (Y2O3), magnesium (Mg) in a range of 1 mol% to 14 mol% in terms of magnesium oxide (MgO), titanium (Ti) in a range of 5 mol% to 10 mol% in terms of titanium oxide (TiO2), and aluminum (Al) in a range of 0.1 mol% to 3 mol% in terms of aluminum oxide (Al2O3), the molar ratio (T / M) of titanium oxide to magnesium oxide is 0.7 to 5.6, and the molar ratio (A / M) of aluminum oxide to magnesium oxide is 0.1 to 0.3, and a solid solution MO of the tetragonal zirconia is formed. X (wherein M is at least Zr, Y, Mg, Ti, and Al) is generated, the number of oxygen atoms X falls within the range of 1.84 to 1.97, thereby solving the above problem. Hafnium (Hf) may further be contained in a range of more than 0 mol % and not more than 1 mol % calculated as hafnium oxide (HfO2). It may further contain silicon (Si) in a range of more than 0 mol % to 3 mol % inclusive, calculated as silicon oxide (SiO2). The Si content may be within the range of 0.1 mol % or more and 0.3 mol % or less in terms of silicon oxide. It may further contain cerium (Ce) and / or calcium (Ca) in a range of more than 0 mol % and not more than 5 mol % calculated as cerium oxide (CeO2) and / or calcium oxide (CaO). At least one element selected from the group consisting of gallium (Ga), germanium (Ge), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), and nickel (Ni) may be further contained in an amount greater than 0 mol % and less than 2 mol % in terms of metal or semi-metal. The phase other than tetragonal zirconia (ZrO2) may be at least one phase selected from the group consisting of oxides, silicides, carbides, nitrides, and borides of the metal elements contained except Zr. The Y may be in the range of 2 mol% or more and 3 mol% or less in terms of yttrium oxide, the Mg may be in the range of 1 mol% or more and 12 mol% or less in terms of magnesium oxide, the Ti may be in the range of 5 mol% or more and 9 mol% or less in terms of titanium oxide, and the Al may be in the range of 0.1 mol% or more and 2.5 mol% or less in terms of aluminum oxide. The Y may be in the range of 2.5 mol% or more and 2.7 mol% or less in terms of yttrium oxide, the Mg may be in the range of 4 mol% or more and 8 mol% or less in terms of magnesium oxide, the Ti may be in the range of 6 mol% or more and 7.5 mol% or less in terms of titanium oxide, and the Al may be in the range of 0.5 mol% or more and 1.5 mol% or less in terms of aluminum oxide. The molar ratio (T / M) of the titanium oxide to the magnesium oxide may be in the range of 0.9 or more and 1.6 or less, and the molar ratio (A / M) of the aluminum oxide to the magnesium oxide may be in the range of 0.15 or more and 0.18 or less. The number of oxygen atoms X may be in the range of 1.89 or more and 1.93 or less. The ceramic may be a sintered body or a semi-sintered body, and the average crystal grain size may be in the range of 50 nm to 300 nm. Effect of the Invention
[0013] The present invention Noji Zirconia ceramics contain 90 vol% or more of tetragonal zirconia (ZrO2), and contain, calculated as oxides, 1 mol% to 4 mol% of yttrium (Y), 1 mol% to 14 mol% of magnesium (Mg), 5 mol% to 10 mol% of titanium (Ti), and 0.1 mol% to 3 mol% of aluminum (Al), which maintains the crystal structure of the zirconia in a tetragonal form and promotes the development of superplasticity.
[0014] Furthermore, the present invention Noji Luconia ceramics has a titanium oxide to magnesium oxide molar ratio (T / M) of 0.7 to 5.6, and aluminium oxide to magnesium oxide molar ratio (A / M) of 0.1 to 0.3. This allows the ceramics to have a melting point of 1×10 -2 This can reduce the minimum temperature at which superplasticity appears in the high strain rate region of 100 / s or more.
[0015] Furthermore, the present invention Noji Zirconia ceramics are a solid solution of tetragonal zirconia. X (where M is at least Zr, Y, Mg, Ti, and Al) is assumed to be generated. By satisfying the range of 1.84 to 1.97, the number of oxygen atoms X can be reduced to reduce the number of heterogeneous compounds and heterogeneous oxide phases that inhibit the development of superplasticity, and the number of oxygen atoms X can be reduced to 1×10 at temperatures of 1350°C or less. -2 / s or higher. [Brief description of the drawings]
[0016] [Figure 1] 1 shows SEM images of the sintered body of Example 2 (A) and the sintered body of Example 4 (B). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The superplastic zirconia ceramic of the present invention is intended to be in the form of a sintered body, semi-sintered body, powder compact, or powder, and may be mainly composed of tetragonal zirconia and may have any form as long as it satisfies the composition described below.
[0018] The amount of the main component is 90 vol% or more. If tetragonal zirconia (ZrO2) is 90 vol% or more, it can exhibit superplasticity through tensile deformation. Whether the zirconia ceramic in question contains 90 vol% or more of tetragonal zirconia can be confirmed from the product of the peak intensity and half-width, which is an approximate value of the integrated intensity of each peak in the X-ray diffraction pattern obtained using an X-ray diffraction measurement device, and the ratio of the integrated intensity of the peak of the tetragonal zirconia phase to the sum of the integrated intensities of all peaks.
[0019] The superplastic zirconia ceramic of the present invention contains at least the following elements: Yttrium (Y) in the range of 1 mol% to 4 mol% calculated as yttrium oxide (Y2O3) Magnesium (Mg) in the range of 1 mol% to 14 mol% calculated as magnesium oxide (MgO) Titanium (Ti) in the range of 5 mol% to 10 mol% calculated as titanium oxide (TiO2) Aluminum (Al) in the range of 0.1 mol% to 3 mol% calculated as aluminum oxide (Al2O3)
[0020] If these elements are less than the above range, zirconia cannot maintain the tetragonal crystal structure and may produce orthorhombic crystal structure. Even if the tetragonal crystal structure is maintained, the effect of promoting superplasticity is lost and the crystal structure is reduced by 1×10 at temperatures of 1350° C. or less. -2 / s or more, a tensile elongation of 200% or more cannot be achieved. Furthermore, if these elements are present in amounts greater than the above range, cubic crystals and even heterogeneous oxide phases are generated and mixed, making it impossible to obtain the superplastic properties described above and the toughness required for tetragonal zirconia.
[0021] The superplastic zirconia ceramic of the present invention further satisfies a molar ratio (T / M) of titanium oxide (TiO2) to magnesium oxide (MgO) of 0.7 to 5.6, and a molar ratio (A / M) of aluminum oxide (Al2O3) to magnesium oxide (MgO) of 0.1 to 0.3. Outside these ranges, the lower limit temperature for superplasticity emergence rises in the high strain rate region, and superplastic properties cannot be obtained below 1350°C.
[0022] The superplastic zirconia ceramic of the present invention further comprises a solid solution of tetragonal zirconia MO X (where M is at least Zr, Y, Mg, Ti, and Al), the number of oxygen atoms X satisfies the range of 1.84 to 1.97. If X is below 1.84, cubic zirconia and one or more different oxides are generated in the structure at 10 vol% or more, which may inhibit the appearance of superplasticity. If X exceeds 1.97, the lower limit temperature for the appearance of superplasticity increases, and superplastic properties cannot be obtained in the high strain rate range at temperatures below 1350°C.
[0023] The X value of a tetragonal zirconia solid solution MOx represents the average number of oxygen atoms bonded (coordinated) to one metal atom, and can be calculated as follows: X = (total number of oxygen atoms) / (total number of metal atoms) = (total mole fraction of oxygen atoms × Avogadro's number) / (total mole fraction of metal atoms × Avogadro's number) = (Σ Number of moles of oxygen atoms in each oxide Ot) / (Σ Number of moles of metal elements in each oxide Mt)
[0024] By satisfying the above-mentioned specific composition and compositional indexes, the superplastic zirconia ceramic of the present invention can achieve a melting point of 1×10 at a temperature of 1350° C. or less. -2 / s or more. Furthermore, the superplastic zirconia ceramic of the present invention can exhibit superplasticity at a lower temperature than conventional materials even in a low to medium strain rate range, for example, in a temperature range of 1150°C to 1200°C.
[0025] The superplastic zirconia ceramic of the present invention may further contain hafnium (Hf) in the range of more than 0 mol % to 1 mol % inclusive, calculated as hafnium oxide (HfO2), which stabilizes the tetragonal zirconia and promotes the development of superplasticity.
[0026] The superplastic zirconia ceramic of the present invention may further contain silicon (Si) in the range of more than 0 mol% to 3 mol% in terms of silicon oxide (SiO2). This stabilizes the tetragonal zirconia, further promoting the development of superplasticity. If the silicon content exceeds 3 mol% in terms of SiO2, an amorphous silica phase may be generated, which may impair the superplastic ductility.
[0027] The Si content is preferably in the range of 0.1 mol % to 0.3 mol % in terms of silicon oxide, which further promotes the development of superplasticity and allows the development of superplasticity in a high strain rate region at temperatures of 1350° C. or less.
[0028] The superplastic zirconia ceramic of the present invention may further contain cerium (Ce) and / or calcium (Ca) in the range of more than 0 mol% to 5 mol% in terms of cerium oxide (CeO2) and / or calcium oxide (CaO). By containing Ce and / or Ca in this range, the formation of cubic zirconia and heterogeneous oxide phases is suppressed, and the acceleration of grain growth during the sintering process or superplastic deformation is suppressed, resulting in excellent superplastic properties while maintaining toughness.
[0029] The superplastic zirconia ceramic of the present invention may further contain at least one element selected from the group consisting of gallium (Ga), germanium (Ge), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), and nickel (Ni) in a range of more than 0 mol% to 2 mol% in terms of metal or semimetal. By containing the above-mentioned elements in this range, the formation of cubic zirconia and different oxide phases is suppressed, and the acceleration of grain growth during the sintering process or superplastic deformation is suppressed, thereby obtaining excellent superplastic properties while maintaining toughness.
[0030] In addition, when the superplastic zirconia ceramic of the present invention further contains at least one element selected from the group consisting of Hf, Si, Ce, Ca, Ga, Ge, Cr, Mn, Fe, Co, and Ni in addition to the main components tetragonal ZrO2, Y, Mg, Ti, and Al, M in the case of assuming a solid solution MOx of tetragonal zirconia is an element further contained in addition to Zr, Y, Mg, Ti, and Al, and the value of X calculated for all of these M's should be in the range of 1.84 to 1.97.
[0031] In the superplastic zirconia ceramic of the present invention, Y, Mg, Ti and Al preferably satisfy the ranges of 2 mol% to 3 mol% in terms of yttrium oxide, 1 mol% to 12 mol% in terms of magnesium oxide, 5 mol% to 9 mol% in terms of titanium oxide, and 0.1 mol% to 2.5 mol% in terms of aluminum oxide, respectively. This allows zirconia to maintain a tetragonal crystal structure and inhibits the generation and mixing of different oxide phases, thereby imparting toughness and further promoting the development of superplasticity.
[0032] In the superplastic zirconia ceramic of the present invention, Y, Mg, Ti and Al more preferably satisfy the ranges of 2.5 mol% to 2.7 mol% in terms of yttrium oxide, 4 mol% to 8 mol% in terms of magnesium oxide, 6 mol% to 7.5 mol% in terms of titanium oxide, and 0.5 mol% to 1.5 mol% in terms of aluminum oxide, respectively. This allows zirconia to maintain a tetragonal crystal structure and further suppresses the generation and mixing of different oxide phases, thereby imparting toughness and further promoting the development of superplasticity.
[0033] In the superplastic zirconia ceramic of the present invention, the molar ratio (T / M) is preferably in the range of 0.9 to 1.6, and the molar ratio (A / M) is preferably in the range of 0.15 to 0.18. -2Tensile elongation of 200% or more can be efficiently achieved at high strain rates of 100 / s or more.
[0034] The X value of the solid solution MOx of tetragonal zirconia preferably falls within the range of 1.89 to 1.93. -2 A tensile elongation of 200% or more can be efficiently achieved even at a high strain rate region of 1 / s or more. In this case, when the superplastic zirconia ceramic of the present invention further contains at least one element selected from the group consisting of Hf, Si, Ce, Ca, Ga, Ge, Cr, Mn, Fe, Co, and Ni in addition to the main components tetragonal ZrO2, Y, Mg, Ti, and Al, M in the case of assuming a solid solution MOx of tetragonal zirconia is an element further contained in addition to Zr, Y, Mg, Ti, and Al, and the value of X may be calculated for all of these M's and satisfy the range of 1.89 to 1.93.
[0035] The phase other than tetragonal zirconia (ZrO2) may be at least one phase selected from the group consisting of oxides, silicides, carbides, nitrides, and borides of metal elements contained other than Zr (including, in addition to Y, Al, Ti, and Mg, elements selected from the group consisting of Hf, Si, Ce, Ca, Ga, Ge, Cr, Mn, Fe, Co, and Ni, as necessary).
[0036] As described above, the superplastic zirconia ceramic of the present invention, by satisfying a specific composition, can achieve a tensile elongation of 200% or more in the high strain rate region at temperatures of 1200° C. to 1350° C. The superplastic zirconia ceramic of the present invention can also exhibit superplasticity at lower temperatures than conventionally in the low to medium strain rate region, for example, in the temperature range of 1150° C. to 1200° C.
[0037] Such superplastic zirconia ceramics can be processed, for example, into a dense sintered body and then subjected to superplastic precision machining, precision sinter forging using a semi-sintered body in which densification has been interrupted, and sinter die forging of powder or compacts before sintering.
[0038] When the superplastic zirconia ceramic of the present invention is a sintered body or semi-sintered body, the average crystal grain size preferably falls within the range of 10 nm to 300 nm. This can promote the development of 200% or more of superplasticity in the medium strain rate range at temperatures of 1350°C or less. The average crystal grain size preferably falls within the range of 50 nm to 150 nm. This can further promote the development of superplasticity in the high strain rate range at temperatures of 1350°C or less. In this specification, the average crystal grain size (d) is a value defined by the following formula with respect to the average intercept length L of a polished sintered body or semi-sintered body in an electron microscope image such as a scanning electron microscope. d=1.56L
[0039] In addition, by combining these techniques, it is possible to bond different ceramics or metal materials, create composite materials, laminate materials, etc. This makes it possible to manufacture engine parts for energy generating devices and high-temperature driving devices that have excellent strength, toughness, heat resistance, and oxidation resistance, heat-resistant precision parts for various heating devices for industrial and consumer use, and substrates and precision parts for electrical and electronic devices.
[0040] Next, an exemplary method for producing the superplastic zirconia ceramic of the present invention will be described.
[0041] For example, when producing a sintered body or semi-sintered body as the superplastic zirconia ceramics of the present invention, a raw material mixture which is a mixture of metal compounds and which can form the above-mentioned composition by firing is fired at a temperature range of 1000°C or higher and 1400°C or lower.
[0042] As the starting material, tetragonal ZrO2 powder, a powder containing Y, a powder containing Mg, a powder containing Ti, and optionally a powder containing at least one element selected from the group consisting of Hf, Si, Ce, Ca, Ga, Ge, Cr, Mn, Fe, Co, and Ni can be used. Instead of the powder containing Y or the powder containing Hf, tetragonal ZrO2 powder to which Y or Hf has been added in advance can be used.
[0043] The powder containing Y may be a single substance or a mixture of two or more substances selected from a Y-containing metal, a silicide, an oxide, a carbonate, a nitride, an oxynitride, a chloride, a fluoride, or an oxyfluoride.
[0044] The powder containing Mg may be a single substance or a mixture of two or more substances selected from a metal, silicide, oxide, carbonate, nitride, oxynitride, chloride, fluoride, or oxyfluoride containing Mg.
[0045] The powder containing Ti may be a single substance or a mixture of two or more substances selected from a metal, silicide, oxide, carbonate, nitride, oxynitride, chloride, fluoride, or oxyfluoride containing Ti.
[0046] If necessary, the powder containing an element selected from the group consisting of Hf, Si, Ce, Ca, Ga, Ge, Cr, Mn, Fe, Co and Ni may be a single substance or a mixture of two or more substances selected from metals, silicides, oxides, carbonates, nitrides, oxynitrides, chlorides, fluorides and oxyfluorides of these selected elements. Alternatively, polysilica may be used as Si.
[0047] If such starting materials are mixed to satisfy the above-mentioned composition, the raw material mixture is molded and sintered to obtain, for example, a sintered or semi-sintered superplastic zirconia ceramic. For molding, die pressing, cold isostatic (isostatic) processing, etc. can be used. For sintering, firing may be performed by a method selected from the group consisting of high-frequency heating, spark plasma sintering (SPS), atmospheric sintering, hot press (HP) sintering, and hot isostatic pressing (HIP) sintering. When atmospheric sintering is used, sintering may be performed in two stages in air. When high-frequency heating, spark plasma sintering (SPS), etc. are used, fine grains are possible, so that the limit temperature in the high strain rate region can be further reduced (for example, to 1150°C).
[0048] For example, when producing a powder as the superplastic zirconia ceramic of the present invention, the raw material mixture may be mixed so as to satisfy the above-mentioned composition, and when producing a powder compact, the raw material mixture may be compacted.
[0049] The present invention will now be described in detail with reference to specific examples, but it should be noted that the present invention is not limited to these examples. EXAMPLES
[0050] [Example 1 to Example 15] In Examples 1 to 15, sintered bodies were produced using appropriate amounts of MgO powder (manufactured by Ube Materials), Al2O3 powder (manufactured by Taimei Chemical Industry), TiO2 powder (manufactured by Showa Denko), 2-3 mol Y2O3 stabilized ZrO2 (Y-TZP, manufactured by Tosoh Corporation), and colloidal polysilica (manufactured by Nissan Chemical Industry).
[0051] In detail, the raw material powders were appropriately weighed so as to obtain the compositions and compositional indexes shown in Table 1, and the powders were compressed and molded by a ball mill, followed by drying and sieving, and then subjected to isostatic pressing (pressure: 400 Pa). The powder compacts of Examples 1 to 9 were sintered in two stages in the air at the temperatures shown in Table 1 (normal pressure sintering). The powder compacts of Examples 10 to 15 were heated in the air at 1050°C to 1250°C. In Table 1, the T / M ratio is the molar ratio of titanium oxide to magnesium oxide, and the A / M ratio is the molar ratio of aluminum oxide to magnesium oxide.
[0052] [Table 1]
[0053] The sintered bodies thus obtained were all dense sintered bodies having a width of 15 mm, a length of 40 mm, and a thickness of 5 mm, and a relative density (Archimedes method) of 98% or more. The tetragonal zirconia content of the sintered bodies of Examples 1 to 15 was examined using an X-ray diffraction apparatus (Rigaku, model number RINT-2200), and all were 90 vol% or more. Phases other than tetragonal zirconia were all oxide phases.
[0054] The obtained sintered bodies of Examples 1 to 15 were observed using a scanning electron microscope (SEM, Hitachi High-Technologies Corporation, model number SEM-SU8000). The results are shown in FIG. FIG. 1 shows SEM images of the sintered body of Example 2 (A) and the sintered body of Example 4 (B).
[0055] According to Fig. 1, it was found that the sintered bodies of Examples 2 and 4 were dense sintered bodies without voids. In addition, when the average crystal grain size was calculated, it was 130 nm in both cases, which was within the range of 50 nm to 150 nm. Although not shown, the other sintered bodies also showed the same state.
[0056] Flat plate-type tensile test pieces with a parallel portion of 3.5 mm wide, 3 mm thick, and 20 mm long were cut out from the sintered bodies of Examples 1 to 15, and high-temperature tensile tests were performed in air at various temperatures and at various strain rates. The results are shown in Table 2.
[0057] [Table 2]
[0058] As shown in Table 2, the material contains 90 vol% or more of tetragonal zirconia (ZrO2), yttrium (Y) in the range of 1 mol% to 4 mol% in terms of yttrium oxide (Y2O3), magnesium (Mg) in the range of 1 mol% to 14 mol% in terms of magnesium oxide (MgO), titanium (Ti) in the range of 5 mol% to 10 mol% in terms of titanium oxide (TiO2), and aluminum (Al) in the range of 0.1 mol% to 3 mol% in terms of aluminum oxide (Al2O3), with a molar ratio (T / M) of 0.7 to 5.6 and a molar ratio (A / M) of 0.1 to 0.3. The material is a solid solution MO of tetragonal zirconia. X (wherein M is at least Zr, Y, Mg, Ti, and Al) is generated, the number of oxygen atoms X is in the range of 1.84 to 1.97. All of the sintered bodies of Examples 1 to 5 have a 1×10 -2At high strain rates of 100 / s or more, a fracture elongation (tensile elongation) of more than 200% was achieved, confirming the occurrence of high-speed superplasticity.
[0059] In particular, it was found that the sintered bodies of Examples 2 to 4 exhibited high-speed superplasticity at temperatures between 1225°C and 1250°C, which is 100°C to 250°C lower than the limit temperature (1350°C) of the conventional technology. Surprisingly, the sintered body of Example 4 exhibited a high-speed superplasticity of 2×10 -1 High-speed superplasticity was also observed at ultra-high strain rates of up to 100 / s (this value is more than 10 times the high-speed limit strain rate of conventional technology).
[0060] Furthermore, when a raw material mixture of the same composition as in Example 2 was compacted, heated for a short time at 1225°C, and then sintered at 1050°C, a sintered body with an average crystal grain size of 100 nm was obtained. When this sintered body was subjected to a high-temperature tensile test in the same manner, the occurrence of high-speed superplasticity was confirmed at 1200°C. This shows that in the case of sintered or semi-sintered ceramics, the average crystal grain size is preferably in the range of 50 nm to 150 nm.
[0061] On the other hand, when focusing on the sintered bodies of Examples 6 to 9, which have the same constituent elements as the sintered bodies of Examples 1 to 5 but have different compositions or composition indices, even at 1350°C or 1400°C, the sintered bodies have a temperature of 1×10 -2 No superplasticity was observed at high strain rates above 100 / s.
[0062] In addition, when the sintered bodies of Examples 10 to 15, which have different compositions from the sintered bodies of Examples 1 to 5 but are similar tetragonal zirconia, are considered, they all have a 1×10 -2 No superplasticity was observed at high strain rates above 100 / s.
[0063] Although not shown, the sintered bodies of Examples 1 to 5 have a melting point of 1×10 -4 / s or more 1×10 -3Superplasticity was observed in the low to medium strain rate range below 1 / s.
[0064] As explained above, the main phase is tetragonal zirconia (ZrO2), and it contains Y, Mg, Ti, and Al in a specific composition ratio, the molar ratio (T / M) is 0.7 to 5.6, and the molar ratio (A / M) is 0.1 to 0.3. The solid solution MO of tetragonal zirconia is X It was shown that the number of oxygen atoms X, assuming the formation of the alloy containing at least Zr, Y, Mg, Ti, and Al, is effective in realizing high speed superplasticity when it is in the range of 1.84 to 1.97. [Industrial Applicability]
[0065] The zirconia ceramic of the present invention can exhibit superplasticity at lower temperatures and in the range of medium to high strain rates compared to conventional techniques, which is expected to lead to industrial applications such as superplastic near-net forming of zirconia ceramics and high-temperature plastic joining of zirconia ceramics with other ceramics and metal materials.
Claims
1. Tetragonal zirconia (ZrO 2 ) at 90 vol % or more, Yttrium oxide (Y 2 O 3 ) in the range of 2 mol % to 3 mol % inclusive, Magnesium (Mg) in the range of 4 mol % to 8 mol % in terms of magnesium oxide (MgO); Titanium oxide (TiO 2 Titanium (Ti) in the range of 6 mol % to 7.5 mol % in terms of Ti; Aluminum oxide (Al 2 O 3 ) in the range of 0.5 mol % or more and 1.5 mol % or less, Contains The molar ratio of titanium oxide to magnesium oxide (T / M) is 0.7 or more and 2.0 or less, the molar ratio of aluminum oxide to magnesium oxide (A / M) is in the range of 0.1 or more and 0.3 or less; The tetragonal zirconia solid solution MO X (wherein M is at least Zr, Y, Mg, Ti, and Al) is formed, the number of oxygen atoms X is in the range of 1.84 to 1.
97.
2. Hafnium oxide (HfO 2 The zirconia ceramic according to claim 1, further comprising hafnium (Hf) in a range of more than 0 mol% and not more than 1 mol% in terms of Hf.
3. Silicon oxide (SiO 2 The zirconia ceramic according to claim 1 or 2, further comprising silicon (Si) in a range of more than 0 mol% and not more than 3 mol% in terms of Si (calculated as zirconia).
4. The zirconia ceramic according to claim 3 , wherein the Si content is in the range of 0.1 mol % or more and 0.3 mol % or less in terms of silicon oxide.
5. Cerium oxide (CeO 2 5. The zirconia ceramic according to claim 1, further comprising cerium (Ce) and / or calcium (Ca) in an amount of more than 0 mol% and not more than 5 mol% calculated as calcium oxide (CaO).
6. The zirconia ceramic according to any one of claims 1 to 5, further comprising at least one element selected from the group consisting of gallium (Ga), germanium (Ge), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), and nickel (Ni) in an amount greater than 0 mol% and less than 2 mol% in terms of a metal or semimetal.
7. Tetragonal zirconia (ZrO 2 7. The zirconia ceramic according to claim 1, wherein the phase other than the above-mentioned phase is at least one phase selected from the group consisting of oxides, silicides, carbides, nitrides, and borides of metal elements contained therein except Zr.
8. a molar ratio (T / M) of the titanium oxide to the magnesium oxide satisfies 0.9 or more and 1.6 or less; The zirconia ceramic according to any one of claims 1 to 7, wherein a molar ratio (A / M) of said aluminum oxide to said magnesium oxide is in the range of 0.15 or more and 0.18 or less.
9. The zirconia ceramic according to any one of claims 1 to 8, wherein the number X of oxygen atoms is in the range of 1.89 or more and 1.93 or less.
10. The ceramic is a sintered body or a semi-sintered body, The zirconia ceramic according to any one of claims 1 to 9, wherein the average crystal grain size is in the range of 50 nm or more and 300 nm or less.
Citation Information
Patent Citations
Antistatic zirconia ceramic and preparation method thereof
CN108821766A
Superplastic deformable zirconium oxide ceramics having high strength
JP1991237059A
Nonlinear ceramics
JP1993339045A
Superplastic zirconia-based sintered body and method for shaping the same
JP2001146469A
Zirconia-based super plasticity ceramic
JP2004107156A